The Importance of Sustainable Waste Management Due to Socio-Economic Changes - Sasana, Hadi; Prasetyanto, Panji Kusuma; Priyono, Nuwun; Novitaningtyas, Ivo (International Journal of Energy Economics and Policy, 2022)
Environmental pollution due to garbage never ends because waste is related to human activities. This study aims to analyze the impact of economic and social activities on environmental pollution in the form of waste generation. Using secondary data for a period of 20 years (2000-2019), with panel data regression analysis techniques. The results showed that the volume of waste generation was more dominated by economic factors, namely industrial activities and the increasing income per capita of the community. Meanwhile, the social aspect that drives the increase in waste generation is the increase in population.